Pengaruh Penggunaan Model Pembelajaran (STAD) Terhadap Hasil Belajar Afektif (Sikap Kerjasama) Kelas III SDN Paterongan 2 - Achmad Khuzairi (Pusat Riset dan Inovasi Nasional, 2023)
The aim of the researcher was to determine the effect of using the Student Teams Achievement Division (STAD) learning model in increasing the Affective Learning Outcomes (Cooperation Attitude) of class III students. This study used a quantitative method with a Quasi-Experimental Design Type of Pre-Observation Post-Observation. The population of this study were third grade students at Paterongan 2 Public Elementary School for the 2022/2023 Academic Year. Sampling using Nonprobability Sampling saturated sample types. The sample of this research is 19 students. Data was collected using observation sheets of students' cooperative attitudes, learning implementation plan sheets. The results showed that there was an influence of the Student Teams Achievement Division (STAD) learning model in increasing students' affective learning outcomes (cooperation attitude) through the results of the pared sample t test (0.00 <0.05).